Experiences and happiness: The role of gender. Issue 8 (27th May 2022) - Brakus, J. Joško; Chen, Weifeng; Schmitt, Bernd; Zarantonello, Lia
Abstract: It is well established that experiences make people happy, but we still know little about how individual differences affect the relationship between consumption of experiences and happiness. This study focuses on gender as the predictor of happiness and addresses the following question: Do women and men differ in the way they attain happiness from consumption of experiences? Considering that research shows that women and men differ in how they process information, it is possible that they differ in how much they reflect on an experience too. Therefore, this study also investigates how the relationship between consumption of experiences and gender is moderated by Need for Cognition (NFC) in affecting subjective happiness. The results of a survey of adult consumers show than women derive more happiness and life satisfaction from meaningful experiences than men whereas men derive more happiness and satisfaction with life from pleasurable experiences than women. NFC moderates these results. The study provides evidence for the distinction between pleasure and meaning in consumption contexts and for the important role of gender in consumption of experiences. Its results imply that design and structuring of commercial experiences should take customer gender into account.